Evaluation of kharif Forage Crops for Biomass Production and Nutritional Parameters in Indo-Gangetic Plains of India - Hindoriya, Phool Singh; Meena, Rajesh Kumar; Singh, Magan; Kumar, Rakesh; Ram, Hardev; Meena, Vijendra Kumar; Kushwaha, Manish (Indian Journal of Animal Nutrition, 2019)
The field experiment was conducted during Kharif, 2017 at Research farm of Agronomy Section, ICAR-NDRI, Karnal. The experiment was laid out in randomized complete block design with eight treatments and three replications. Among eight treatments two perennial forage crops NBH, guinea grass cultivated sole as well as intercropping with cowpea and four seasonal fodder crops (cowpea, sorghum, baby corn and maize) were tested. Experimental results showed that among the different fodder crops, the highest DM content was recorded in the intercropped guinea grass (25.1%) with cowpea in the 2:3 row ratio followed by sole guinea grass (24.9%) while lower in cowpea (16.9%). Protein, ether extract and total ash yield were statistically significant higher in the intercropping of NBH + cowpea (14.46 q/ha), (3.28 q/ha) and 13.07 q/ha, respectively). The higher ADF content was observed in the sorghum sole (41.6%), followed by guinea sole (40.1%) while, lower in sole maize (35.3%) and it was statistically significant from sole sorghum and guinea forage crops. The higher value of NDF was recorded in the sole guinea grass (71.16%) which was significantly higher over the other treatments. The ADL was found highest in the sole cowpea (8.68%).Â